Simple speech controlled home automation system using android devices - Theodore Ramli; Natashia Nabiha Dabimel; Mazlina Mamat; Norfarariyanti Parimon; Rosalyn R. Porle (2016)
Speech control is an emerging innovative method to accomplish control tasks. In this work, a system is created to control two of the most human interactive activities; switching on and off of lights and fans using ATMEGA-328P microcontroller and Android OS’ speech recognition. This system improves the living standard by making life easier and increasing productivity. The development of the prototype will be made within a low budget in hopes to attract people.